The chemical manipulation of meta-stable brine super-saturated with gypsum: forcing precipitation by overriding the inhibitory effect of antiscalants on crystal formation. - Gerber, Daniel Hendrik (Stellenbosch : Stellenbosch University, 2011)
Thesis (MScEng)--Stellenbosch University, 2011.